2016
DOI: 10.1002/ange.201511883
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Core‐Modification of a Porphyrin into an Antiaromatic Isophlorin

Abstract: Partial core-modification of ap orphyrin can be employed to synthesize the 20p antiaromatic isophlorin. Unlike the tetra-, tri-, and dipyrrole derivatives of aporphyrin, amonopyrrole porphyrin exhibits antiaromatic characteristics. It undergoes at wo-electron reversible ring oxidation to yield the 18p aromatic dication. 1 HNMR analysis provides distinct evidence of the altered electronic characteristics through typical paratropic and diatropic ring current effects for the 4n and the (4n + 2) p-electron systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…R N Mukherjee and his group at Kanpur, have contributed significantly to the development of broadbased synthetic coordination chemistry of transition metal ions with designed organic ligands to address shown that a monopyrrole porphyrin exhibits antiaromatic characteristics (Panchal et al, 2016).…”
Section: Coordination Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…R N Mukherjee and his group at Kanpur, have contributed significantly to the development of broadbased synthetic coordination chemistry of transition metal ions with designed organic ligands to address shown that a monopyrrole porphyrin exhibits antiaromatic characteristics (Panchal et al, 2016).…”
Section: Coordination Chemistrymentioning
confidence: 99%
“…Recently, a selenabenzoporphyrin and its Pd(II) complex were synthesized and characterized . Anand and co-workers have been involved in the synthesis of large porphyrin-like macrocycles with a view to studying concepts such as aromaticity and anti-aromaticity (Panchal et al, 2016), (Gopalakrishna et al, 2014). Panda and co-workers have been working on various porphyrin-based macrocycles including isomeric porphyrins (Sarma et al, 2015).…”
Section: Coordination Chemistrymentioning
confidence: 99%
“…Air‐stable macrocycles with an isophlorin like conjugation bearing 20π electrons have been synthesized with heterocycles such as furan and thiophene [21] . A 20π core‐modified porphyrin, 5 a , and a few expanded porphyrins, 7 a , are known to adopt an isophlorin‐like conjugation [22,23] . Significantly, isophlorinoids are susceptible to either reversible two‐electron ring oxidation or proton‐coupled electron transfer (PCET) involving more than two electrons (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, isophlorinoids are susceptible to either reversible two‐electron ring oxidation or proton‐coupled electron transfer (PCET) involving more than two electrons (Figure 2). For example, a 20π antiaromatic mono‐pyrrole isophlorin 5 a resists PCET and is more susceptible to ring oxidation to yield the 18π dicationic aromatic species 5 b [22] . A non‐pyrrolic expanded 32π hexaoxa non‐antiaromatic isophlorinoid 6 a undergoes reversible ring oxidation to yield a planar 30π dicationic aromatic species 6 b [24] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these macrocycles do not exhibit typical reversible oxidations in cyclic voltammetry (ESI†) as expected for 4 n π porphyrinoids. 27 This can be attributed to the cross conjugation arising due to the successive α, β links of thiophene units in the macrocycle.…”
mentioning
confidence: 99%